Mrs. Brown [videorecording (DVD)] - Madden, John, 1949-; Brock, Jeremy, 1959-; Curtis, Sarah; Dench, Judi, 1934-; Connolly, Billy; Sher, Antony, 1949-2021; Palmer, Geoffrey, 1927-2020; Pasco, Richard; Westhead, David, 1963- (Miramax / Paramount, 2021)
Queen Victoria was the world's most powerful woman. Rugged Scotsman John Brown was a lowly servant who looked after her horses. Yet when circumstances brought them together the result was a passionate friendship that scandalized a nation.